HEALTHCARE UTILIZATION FOR ACUTE RESPIRATORY INFECTIONS DURING THE COVID-19 PANDEMIC AND ASSOCIATED FACTORS: A CROSS- SECTIONAL STUDY IN SOUTH DENPASAR, INDONESIA - Luh Putu Kartiningsih; I Ketut Swarjana; AAA Yuliati Darmini; Made Dian Shanti Kusuma (Nurse and Health: Jurnal Keperawatan, 2023)
Background: Acute respiratory infections (ARIs) are the leading cause of morbidity and mortality among children globally, and require early diagnosis and intervention. During the COVID-19 pandemic, ARI healthcare utilization has been a challenge. Objectives: This study aimed to determine healthcare utilization for ARI during the COVID-19 pandemic, and the associated factors among children aged under five years. Methods: A cross-sectional study was conducted in South Denpasar District, Indonesia. It involved 221 mothers of children aged under five years with ARIs, selected using probability proportional to size. Data were collected through a questionnaire and analyzed using descriptive statistics to measure frequency and proportion, along with multiple logistic regression to determine the factors associated with healthcare utilization of ARI. Results: Among 221 respondents, the majority (65.6%) utilized ARI healthcare in the health centers. Mother’s age (OR: 0.21; p=0.041), number of children (OR: 4.79; p=0.001), occupation (OR: 0.38; p=0.002), and distance traveled (OR: 2.37; p=0.008) were associated with utilization of ARI healthcare. Conclusion: The healthcare utilization for ARI during the COVID-19 pandemic was low. Therefore, improved utilization is needed by using local health centers, mobile services, and home visits.